LEVERAGE AND LIQUIDITY ON DIVIDEND POLICY - Joseph Philip Kambey; Isye Pongoh; stanny sicilia rawung (STIE AMKOP, 2019)
The purpose of this research is to find out the influence of Leverage (DER) and Liquidity (CR) on dividend policy especially of LQ-45 listed manufacturing companies on Indonesia Stock Exchange. The sample was taken using purposive sampling method and the sample fulfilled the criteria of ten manufacturing companies. The data used were secondary data, namely the financial statements of companies that have gone public and LQ-45 listed on the Indonesia Stock Exchange in the period of August 2017. The data analysis techniques using panel data regression, test coefficient of determination, T test and F test shows that Leverage (DER) has a negative and insignificant effect on dividend and liquidity (CR) has a positive and insignificant effect. For determination coefficient test, R2 value is 0.422502 which means that the combination of independent variable is able to explain dependent variable equal to 42% while the remaining 58% is explained by other factors outside the research model.